Using online flipped classroom in problem-based learning medical curriculum: A mixed method study - Dian Nugroho; Bulan Kakanita Hermasari (Intelektual Pustaka Media Utama, 2023)
The coronavirus disease (COVID-19) pandemic has changed the education system, including problem-based learning (PBL), which is the main curriculum model in medical education. Social interaction and acquisition of knowledge and skills are one of the challenges in online learning during a pandemic. This study evaluated the use of the flipped classroom in the PBL curriculum of medical education. This study used mixed-methods design with a concurrent approach. The data collection technique was secondary data collection in the form of data from the block learning evaluation form. The evaluation form contains statements regarding the quality of the learning process, in the form of Likert scales. At the end of the form, there was a fill-in/essay question for more in-depth exploration. The quantitative data were analysed using descriptive univariate analysis, meanwhile, the qualitative data were analysed using thematic analysis techniques. Unbalanced learning load on the block, block learning management, and knowledge retention in block learning were considered lacking in flipped classroom block implementation. The management of time delays, a stage for students to be ready, a step to lessen psychological stress, and the use of media to generate different learning experiences are particular areas that need improvement.